Extensible hierarchical codec semantic communication system - Yuyuan ZHANG; Haitao ZHAO; Jibo WEI; Kuo CAO; Yichi ZHANG; Peng LUO; Yueling LIU; Kai MEI (Tongxin xuebao)
Aiming at the problem that most current researches on text semantic communication mainly rely on simulation system for theoretical verification, an extensible hierarchical semantic communication system was proposed by taking advantage of the separation of hierarchical encoding and decoding architecture in semantic level and grammatical level.The system was compatible with the reliable communication technology under the framework of Shannon information through the mode of semantic and syntactic separation, and realized the nested combination of semantic communication and traditional communication.Furthermore, a universal and extensible verification system was built based on the software radio platform to verify the proposed semantic communication system architecture.The verification system took semantic communication software platform as the driving core of hardware drive and algorithm call, integrated the whole process of signal generation, information transmission, data acquisition, decoding and evaluation at the receiving end, and could be further extended for semantic and syntactic level.Finally, the text semantic communication was tested based on this verification system, which verified that it had higher validity and reliability than the traditional communication mode.